2020
DOI: 10.3390/toxins12120801
|View full text |Cite
|
Sign up to set email alerts
|

Antitoxin ε Reverses Toxin ζ-Facilitated Ampicillin Dormants

Abstract: Toxin-antitoxin (TA) modules are ubiquitous in bacteria, but their biological importance in stress adaptation remains a matter of debate. The inactive ζ-ε2-ζ TA complex is composed of one labile ε2 antitoxin dimer flanked by two stable ζ toxin monomers. Free toxin ζ reduces the ATP and GTP levels, increases the (p)ppGpp and c-di-AMP pool, inactivates a fraction of uridine diphosphate-N-acetylglucosamine, and induces reversible dormancy. A small subpopulation, however, survives toxin action. Here, employing a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
(112 reference statements)
1
4
0
Order By: Relevance
“…At the same time, in all the infection curves of the ATCC10031/pCA24N ( pemK ) strain, we observed a reversible effect of viral cycle arrest, similar to that shown by Moreno del-Aramo et al. 2020 40 . Indeed, after 3 h post-infection the phages were able to infect the strain, resulting in a decrease in the OD 600nm (opposite effect to that observed in the presence of IPTG induction and absence of phage infection) and an increase in phage counts (PFU/mL).…”
Section: Discussionsupporting
confidence: 89%
“…At the same time, in all the infection curves of the ATCC10031/pCA24N ( pemK ) strain, we observed a reversible effect of viral cycle arrest, similar to that shown by Moreno del-Aramo et al. 2020 40 . Indeed, after 3 h post-infection the phages were able to infect the strain, resulting in a decrease in the OD 600nm (opposite effect to that observed in the presence of IPTG induction and absence of phage infection) and an increase in phage counts (PFU/mL).…”
Section: Discussionsupporting
confidence: 89%
“…Bacteria have evolved complex regulatory controls and multiple cellular transition states in response to a variety of environmental stresses. In order to survive, cells slow down their growth rate and redirect their metabolic resources until conditions are such that growth can be resumed [ 29 , 30 ]. The transcriptional activation mechanism of the TA system is essential for bacterial persistence, and although the mechanism of action can vary greatly and different DNA-binding domains and transcriptional regulatory mechanisms can be found even among members of the same TA family, toxin activity is diverse regardless of TA function and has been shown to interfere with basic cellular function [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…cells that become dormant or have a reduced growth rate and become highly tolerant to bactericidal antibiotics (Lioy et al 2012 , Wen et al 2014a , b , Paul et al 2019 , Zhang et al 2020 , Singh et al 2021 , Sonika et al 2023 ). Furthermore, transient toxin Zeta expression reduced the growth rate and inhibited phage SPP1 intracellular amplification, and the phage infective cycle resumed after the expression of antitoxin Epsilon (Moreno-del Álamo et al 2020 ). We have to consider that some of the ‘classical’ points of view on virulence and pathogenesis can be questionable because they can be due to the over-response of the host (i.e.…”
Section: Bacterial Ta Operonsmentioning
confidence: 99%
“…The roles of epsilon–zeta proteins and further details concerning their relevance have been recently analysed in-depth (Moreno-del Álamo et al 2019 , 2020 ; and references therein), and thus, we shall not pursue this tripartite-TA further. The toxic effect of PezT was assayed in E. coli and it was shown that overproduction of the toxin resulted in cell growth arrest for as long as 180 min, but growth could be restored by synthesis of the PezA antitoxin (Khoo et al 2007 ), indicating that only overproduction of the toxin could be lethal.…”
Section: The S Pneumoniae Pezat Operonmentioning
confidence: 99%